Twelve millennia : archaeology of the upper Mississippi River Valley - Theler, James L., 1946- (Bur oak book., 2003)
The people of Taquile Island on the Peruvian side of beautiful Lake Titicaca, the highest navigable lake in the Americas, are renowned for the hand-woven textiles that they both wear and sell to outsiders. One thousand seven hundred Quechua-speaking peasant farmers, who depend on potatoes and the fish from the lake, host the forty thousand tourists who visit their island each year. Yet only twenty-five years ago, few tourists had even heard of Taquile.